Current advancements and potential strategies in the development of MERS-CoV vaccines - Zhang, Naru (Expert Rev Vaccines, 2014)
Middle East respiratory syndrome (MERS) is a newly emerging infectious disease caused by a novel coronavirus, MERS-coronavirus (MERS-CoV), a new member in the lineage C of β-coronavirus (β-CoV). The increased human cases and high mortality rate of MERS-CoV infection make it essential to develop safe and effective vaccines. In this review, the current advancements and potential strategies in the development of MERS vaccines, particularly subunit vaccines based on MERS-CoV spike (S) protein and its receptor-binding domain (RBD), are discussed. How to improve the efficacy of subunit vaccines through novel adjuvant formulations and routes of administration as well as currently available animal models for evaluating the in vivo efficacy of MERS-CoV vaccines are also addressed. Overall, these strategies may have important implications for the development of effective and safe vaccines for MERS-CoV in the future.